The Effect of Corporate Governance on Tax Avoidance Behavior - Meida Listiyana; Lies Zulfiati; Sharifuddin Husen (BPJP - STEI, 2019)
Abstract—This study aims to determine the effect of corporate governance as proxied by the board of commissioners, audit committee and institutional ownership on tax avoidance behavior that occurs in manufacturing companies listed on the Indonesia Stock Exchange. Tax avoidance in this study uses the residual method to obtain the value of the normal book tax difference. This study adds control variables namely profitability, leverage and company size. The research method used was panel data regression analysis using eviews 10. The sample was determined based on the purposive sampling method with the number of research samples obtained as many as 115 companies during the period 2014-2018. The results in this study showed that: 1) the board of commissioners had no influence towards tax avoidance behavior with a positive coefficient which means that when the effectiveness of the board of commissioners increases it will increase tax avoidance behavior, 2) the audit committee has a significant effect on tax avoidance behavior with a negative coefficient which means that when the effectiveness of the audit committee increases it will reduce tax avoidance behavior, 3) institutional ownership does not affect the behavior of tax avoidance with a negative coefficient which means that when institutional ownership increases it will reduce tax avoidance behavior. The results of the control variable test show profitability affects the behavior of tax avoidance, leverage does not affect the behavior of tax avoidance and the size of the company does not affect the behavior of tax avoidance.